Comprehensive analysis of the complete mitochondrial genomes of three Coptis species (C. chinensis, C. deltoidea and C. omeiensis): the important medicinal plants in China - Zhong, Furong; Ke, Wenjia; Li, Yirou; Chen, Xiaoyan; Zhou, Tao; Xu, Binjie; Qi, Luming; Yan, Zhuyun; Ma, Yuntong (Frontiers in Plant Science, 2023)
Coptis plants (Ranunculaceae) contain high levels of isoquinoline alkaloids and have a long history of medicinal use. Coptis species are of great value in pharmaceutical industries and scientific research. Mitochondria are considered as one of the central units for receiving stress signals and arranging immediate responses. Comprehensive characterizations of plant mitogenomes are imperative for revealing the relationship between mitochondria, elucidating biological functions of mitochondria and understanding the environmental adaptation mechanisms of plants. Here, the mitochondrial genomes of C. chinensis, C. deltoidea and C. omeiensis were assembled through the Nanopore and Illumina sequencing platform for the first time. The genome organization, gene number, RNA editing sites, repeat sequences, gene migration from chloroplast to mitochondria were compared. The mitogenomes of C. chinensis, C. deltoidea and C. omeiensis have six, two, two circular-mapping molecules with the total length of 1,425,403 bp, 1,444,809 bp and 1,152,812 bp, respectively. The complete mitogenomes harbors 68-86 predicted functional genes including 39-52 PCGs, 26-35 tRNAs and 2-4 rRNAs. C. deltoidea mitogenome host the most abundant repeat sequences, while C. chinensis mitogenome has the largest number of transferred fragments from its chloroplasts. The large repeat sequences and foreign sequences in the mitochondrial genome of Coptis species were related to substantial rearrangements, changes in relative position of genes and multiple copy genes. Further comparative analysis illustrated that the PCGs under selected pressure in mitochondrial genomes of the three Coptis species mainly belong to the mitochondrial complex I (NADH dehydrogenase). Heat stress adversely affected the mitochondrial complex I and V, antioxidant enzyme system, ROS accumulation and ATP production of the three Coptis species. The activation of antioxidant enzymes, increase of T-AOC and maintenance of low ROS accumulation in C. chinensis under heat stress were suggested as the factors for its thermal acclimation and normal growth at lower altitudes. This study provides comprehensive information on the Coptis mitogenomes and is of great importance to elucidate the mitochondrial functions, understand the different thermal acclimation mechanisms of Coptis plants, and breed heat-tolerant varieties.